Electrodeposited reduced graphene oxide-PEDOT:PSS/Nafion hybrid interface for the simultaneous determination of dopamine and serotonin - Seunghyeon, KO; Kim, Seung Wook; Lee, Soo Hyun; Yi Jae Lee (Nature Publishing Group, 2023)
The electrochemically deposited reduced graphene oxide-PEDOT:PSS/Nafion (rGO-PP/NF) hybrid material has provided a favorable interface for the simultaneous detection of dopamine (DA) and serotonin (5-HT). The rGO-PP/NF onto the Au seed layer of the flexible substrate was simple, and it was followed by the sequential electrophoretic deposition of GO, reduction at the optimal pH buffer media, electropolymerization of EDOT:PSS, and Nafion coating. The strong electron-transport capacity between rGO-PEDOT:PSS and the negatively charged Nafion matrix might allow the highly sensitive, simultaneous, and selective detection of DA and 5-HT due to its high affinity for cations. In the results of the electrochemical response, well-separated oxidation peaks were observed in a mixture that contained various concentrations of DA and 5-HT. It showed the dynamic sensing of DA and 5-HT in the ranges of 0.5？75 μM and 0.05？50 μM, respectively, and the detection limits of 0.17 and 0.16 μM, respectively. In the mixture of DA and 5-HT, the sensor had a detection limit of 0.1 μM for 5-HT and DA, and its sensitivities of DA and 5-HT were 99.3 and 86 ？A/？Mcm2. Furthermore, it demonstrated high selectivity, reproducibility, stability, and a recovery property in the human serum spike test that was good enough for the practical use.